A Safe and Efficient Strategy for the Rapid Elimination of Blood Lead In Vivo Based on a Capture–Fix–Separate Mechanism. (25th June 2019) - Wan, Mi Mi; Xu, Ting Ting; Chi, Bo; Wang, Meng; Huang, Yangyang; Wang, Qi; Li, Ting; Yan, Wen Qiang; Chen, Huan; Xu, Ping; Mao, Chun; Zhao, Bo; et al.
Abstract: Lead poisoning is an important problem because of its serious effects on human health. Yet a solution is not available due to an incomplete understanding of the state of lead ions in blood. Since most blood lead binds to hemoglobin (Hb) in red blood cells, identifying and capturing lead‐contaminated Hb in RBCs is important. Herein, a magnetic blood lead remover with hyperbranched poly(amidoamine)s (HPAM) as template/co‐adsorbent and core–shell mesoporous structure was synthesized. Lead‐containing Hb was selectively captured and then fixed by mesoporous channels. The magnetic separation technology was used to separate the magnetic remover from blood. A related blood lead clean‐up apparatus was used to remove lead from the blood of a pig in vivo. Results of physical/chemical characterizations, biocompatibility experiments, animal tests, and theoretical simulation verify the safety and efficiency of this removal strategy and the high efficiency of the blood lead clean‐up apparatus. Abstract : Die effiziente Behandlung von Bleivergiftung gelingt mit Fe3 O4 ‐Nanopartikeln, die mit Amin‐angereicherten hyperverzweigten Poly(amidoaminen) beschichtet sind, in Kombination mit einer Apparatur, die die magnetische Entfernung von nanopartikelassoziiertem, bleihaltigem Hämoglobin ermöglicht. Diese Strategie ermöglichte die Entfernung von 75 % des Bleigehalts aus Schweineblut in vivo innerhalb von 50 min.